Descending to Bring Up “The Knowledge of the Son of God”: The Descent–Ascent Use of Psalm 68:18 in Ephesians 4:8–10, Compared with Romans 10:6–8’s Use of Deuteronomy 30 - Benjamin D. Giffone (Religions)
This paper offers a new explanation for the quotation of Psalm 68:18 in Ephesians 4:8. There are at least three puzzles in this text: (1) the significance of the quotation within the argument in the Ephesians passage (and why the apparent interruption between 4:7 and 4:11); (2) the divergent form of the quotation from the MT and LXX vis-a-vis the giving of gifts versus receiving; (3) why is only one set of gifts—proclaiming/verbal gifts, not gifts of service or discernment—mentioned in 4:11–12? This paper argues three points. First, diversity of spiritual gifts is not the focus of Eph 4:7–16, but rather, the same gift given to many: the word of truth about Jesus’s identity as Messiah and Son of God and his resurrection. Second, Ephesians 4:8–10 is comprehensible in context if viewed through another lens: Romans 10:6–8, the motif of “Messiah ascending victorious after having previously descended”. Third, the invocation of Psalm 68:18 in Ephesians 4:8–10 matches the Aramaic textual tradition, over-against the MT and the LXX. Paul’s use of the verse mirrors the proto-Targumic understanding of the “gifts given to the sons of mankind” as the Law of Moses. Paul is adopting this motif of “ascending with the Law-truth”, but with his own implied substitution of “the truth about Jesus”.